Impact of the COVID-19 pandemic on suicide and self-harm among patients presenting to the emergency department of a teaching hospital in Nepal - Shrestha, Roshana (PLoS One, 2021)
The COVID-19 pandemic is a global challenge that is not just limited to the physical consequences but also a significant degree of a mental health crisis. Self-harm and suicide are its extreme effects. We aim to explore the impact of this pandemic on suicide and self-harm in our Emergency Department. A cross-sectional study was conducted including all fatal and nonfatal self-harm patients presenting to the emergency department during the lockdown period (March 24-June 23, 2020; Period1), matching periods in the previous year (March 24-June 23,2019; Period 2) and 3 months period prior (December 24 2019-March 23, 2020; Period 3) were included through the electronic medical record system. The prevalence and the clinical profile were compared between these three periods. A total of 125 (periods 1 = 55, 2 = 38, and 3 = 32) suicide and self-harm cases were analyzed. Suicide and self-harm had increased by 44% and 71.9% during the lockdown in comparison to periods 2 and 3. Organophosphate poisoning was the most common mode. Females were predominant in all three periods with a mean age of 32 (95%CI: 29.3–34.7). There was a significant delay in arrival of the patients in period 1 (p = 0.045) with increased hospital admission (p = 0.003) and in-hospital mortality (18.2% vs 2.6% and 3.1%) (p<0.001). Our study showed an increase in suicide and self-harm cases in the emergency department during the initial phase of the COVID-19 pandemic which may reflect the increased mental health crisis in the community in low resource settings like Nepal. This study highlights the importance of priming all mental health care stakeholders to initiate mental health screening and intervention for the vulnerable population during this period of crisis.